Exploration of Attractive Learning Media: DeBuTon Sounding Book - Telaumbanua, Angeline Berlian Christiana; Daneswari, Kun Faradhillah; Pramesti, Revalina Agdya; Aini, Desti Nur (Nexus Publishing, 2024)
This article discusses the development of a learning media titled